Penerapan Metode Autoregressive Integrated Moving Average (ARIMA) Dalam Memprediksi Jumlah Penjualan Bingkai - Pristiwanto (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2020)
Ektaco Sumber Foto is a company engaged in photo printing and is one of the largest photo labs in , which serves and facilitates photography needs for photographers. Ektaco Sumber Foto serves every day and facilitates the needs of photographers such as photo printing, frames, exclusive albums and press albums. The world of photographers is experiencing very rapid development from the film era to the digital era, which makes consumers increasingly modernize photographer prints with certain designs and sizes and combine them with photo frames. Forecasting is forecasting something that hasn't happened yet. This research was conducted with quantitative forecasting methods. Box-Jenkins Periodic Series (ARIMA) method is a forecasting method that involves statistical analysis of past data. This ARIMA completely ignores the independent variables because this model uses the present values ​​and past values ​​of the independent variables to produce accurate short-term predictions or forecasts. Forecasting is important for every business organization and for every management decision making that is very significant. Forecasting is the basis for a company's long-term planning. The accuracy of the results of business forecasting will increase opportunities for achieving profitable investments in the company.